স্বাধীনতার পটভূমি : ১৯৬০ দশক - হাসান, মোরশেদ শফিউল (ঢাকা : অনুপম প্রকাশনী, 2014)
Articles on political history of Bangladesh, during 1960s.
Includes bibliographical references.
In Bengali.
Keywords: Bangladesh -- Politics and government